The crime of issuing “empty” VAT invoices - Patora, Krystyna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The subject of this article was issuing ‘empty’ invoices, including first and foremost explanation what should be understood under this concept in the jurisprudence of Polish Courts as well as the Tribunal of Justice. Moreover, the subject of consideration covered tax effects concerning the possibility of deducting the sum indicated on the invoice by the recipient of the invoice as well as those for the invoice issuer resulting from article 108 of the act of tax on goods and services. Due to the fact that the legal qualification of these events is not uniformly recognized in jurisprudence and in the doctrine, it has become indispensable to present views in this respect.